2017
DOI: 10.1186/s40317-017-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a low-cost, solar-powered pop-up satellite archival tag for assessing post-release mortality of Atlantic bluefin tuna (Thunnus thynnus) caught in the US east coast light-tackle recreational fishery

Abstract: Background: Pop-up satellite archival tags (PSATs) are a valuable tool for estimating mortality of pelagic fishes released from commercial and recreational fishing gears. However, the high cost of PSATs limits sample sizes, resulting in low-precision post-release mortality estimates with little management applicability. We evaluate the performance of a lower-cost PSAT designed to enable large-scale post-release mortality studies. The tag uses solar rather than battery power, does not include a depth sensor, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…() suggests that new tag attachment methods and/or tag anchors, which minimize injury and potential behavioral effects, may need to be developed for the small‐bodied, laterally compressed spearfishes. In contrast, three studies with successful PSAT data reports from a combined 57 juvenile Atlantic bluefin tuna ( Thunnus thynnus ), which are small in size but have a robust body morphology, documented no tag‐associated post release mortality and only two inferred natural predation events (Galuardi & Lutcavage, ; Goldsmith, Scheld, & Graves, ; Marcek, Fabrizio, & Graves, ). Future work on the Mediterranean spearfish should assess long‐term movement patterns for a large number of individuals, identify additional spawning areas, and determine the species’ population structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() suggests that new tag attachment methods and/or tag anchors, which minimize injury and potential behavioral effects, may need to be developed for the small‐bodied, laterally compressed spearfishes. In contrast, three studies with successful PSAT data reports from a combined 57 juvenile Atlantic bluefin tuna ( Thunnus thynnus ), which are small in size but have a robust body morphology, documented no tag‐associated post release mortality and only two inferred natural predation events (Galuardi & Lutcavage, ; Goldsmith, Scheld, & Graves, ; Marcek, Fabrizio, & Graves, ). Future work on the Mediterranean spearfish should assess long‐term movement patterns for a large number of individuals, identify additional spawning areas, and determine the species’ population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Mediterranean spearfish is a target of secondary importance in the traditional Italian harpoon fishery (Romeo et al, 2015) and rare bycatch in other commercial fisheries ( morphology, documented no tag-associated post release mortality and only two inferred natural predation events (Galuardi & Lutcavage, 2012;Goldsmith, Scheld, & Graves, 2017;Marcek, Fabrizio, & Graves, 2016). Future work on the Mediterranean spearfish should assess long-term movement patterns for a large number of individuals, identify additional spawning areas, and determine the species' population structure.…”
Section: Discussionmentioning
confidence: 99%
“…; Marcek and Graves ; Goldsmith et al. ), suggesting that catch‐and‐release angling is a viable conservation strategy that would provide substantial benefits, especially to high‐income anglers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the additional value attached by class 1 anglers to nonconsumptive aspects of Bluefin Tuna fishing (catch and release, hooking and losing fish, and other factors captured by the ASC) appear to provide sufficient incentive for this group to continue targeting Bluefin Tuna despite restrictive harvest regulations. Studies using pop-up satellite archival tags have indicated that postrelease mortality of Bluefin Tuna released in recreational fisheries is low (<5%) across size-classes (Stokesbury et al 2011;Marcek and Graves 2014;Goldsmith et al 2017), suggesting that catch-and-release angling is a viable conservation strategy that would provide substantial benefits, especially to high-income anglers.…”
mentioning
confidence: 99%
“…The number of papers researching energy harvesting from the non-human animal body is limited. Solar harvesting research was performed on zebras [21], north elephant seals [22], tuna [23], pink iguanas [24], turtles [25], and cattle [26]. Some limited research with thermoelectric energy harvesting of sheep has been performed [27].…”
Section: Animal Kinetic Energy Harvesting and The Animal Wearables Ma...mentioning
confidence: 99%